Adult Lactose Digestion Status and Effects on Disease - Andrew Szilagyi (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Adult assimilation of lactose divides humans into dominant lactase-persistent and recessive nonpersistent phenotypes.